Dexmedetomidine for sedation in intensive care. Literature review and clinical experience (Perioperaciina Medicina, 2020)
Dexmedetomidine is a fairly new and promising drug for use in intensive care and surgery. Due to the fact that it is an agonist of alpha-2-adrenoceptors, dexmedetomidine has an analgesic, sedative effect and affects hemodynamic parameters. Due to the fact that dexmedetomedin does not have the ability to suppress respiration, it is used in patients with respiratory disorders. Dexmedetomidine has minimal side effects and a wide range of uses.
Keywords: dexmedetomidine; sedation; pain; intensive care; sleep; delirium